TEST OF BIODIESEL FROM USED COOKING OIL FROM DORMITORY X ON OPACITY AND EXHAUST EMISSIONS HC, CO AND CO2 - Budi Sulistiyo Nugroho; Silvya Yusnica Agnesty; Haris Numan Aulia; Heni Fidyaningrum (PENDIDIKAN SAINS DAN TEKNOLOGI, 2023)
The current trend is the use of biodiesel as an alternative fuel, one alternative is used cooking oil. Not many Indonesian people are aware of the great potential for utilizing used cooking oil or what is commonly called cooking oil (waste vegetable oil or WVO, also known as waste cooking oil or WCO and used cooking oil or UCO). The aim is to minimize pollution of used/used cooking oil waste in the surrounding environment as environmental conservation, to know the characteristics and quality requirements of used cooking oil/used cooking oil from dormitory X to become biodiesel according to SNI 04-7182-2015 standards, as well as the effect of blending biodiesel from cooking oil used/used cooking oil from dormitory X with PT Pertamina's Solar TBBM on opacity, performance and exhaust emissions of diesel engines. Test results for used cooking oil test criteria for smell, taste, visual color, water content, free fatty acids, acid number and peroxide value do not meet the quality standards of SNI 01-3741-2002, so they are not suitable for use or consumption again because they are toxic. The highest yield value is 81.33% and the lowest is 61.7%. Analysis of the FAME content was 98.18% and the remaining 0.72% glycerol. The highest content of methyl palmitate was 47.57% and the lowest content was 1.502% methyl myristate. Density test results were 815 – 880, viscosity were 2.3 – 6.0 cST, water content were 210,667 – 366,750, ASTM Copper Strip color test and copper blade corrosion were sequentially number 3 and class 1 A. The highest opacity value was achieved at 3000 rpm rotation . Emissions of hydrocarbons (HC) produce no HC on average. Carbon monoxide (CO) exhaust emissions produce an average of 0.05% by volume. Emission levels of CO2 in exhaust gas show an average of 0.2% by volume.